Perbedaan Pengetahuan Kontrol Plak Berdasarkan Jenis Kelamin Mahasiswa Profesi Kedokteran Gigi Universitas Jenderal Achmad Yani - Andi Supriatna; Shanaya A. Anindyta; Marlin Himawati (e-GiGi, 2023)
Abstract: Dental and oral diseases especially problems related to dental plaque are still commonly found in Indonesia. Therefore, plaque control is an effective way to treat and prevent these diseases. This study aimed to obtain the difference in knowledge regarding plaque control based on sex (male and female) among students of the dentistry profession of Universitas Jenderal Achmad Yani. This was an analytical and observational study with a cross sectional design. Samples were chosen using consecutive sampling technique. A non-specialized design of unpaired numerical categorical analysis was used in this study. The google form was used as instrument. Data were analysed using the unpaired T-test. The results showed that there were 116 dentistry profession students as respondents consisting of 32 males (27.6%) and 84 females (72.4%). Based on sex, the knowledge regarding plaque control showed that the average in male respondents was 21.50±7.030 and in female respondents was 22.82±5.928 (a p-value of 0.311). In conclusion, there is no difference in the knowledge of plaque control among male and female students of the dentistry profession of Universitas Jenderal Achmad Yani. Keywords: sex; knowledge of plaque control Abstrak Penyakit gigi dan mulut masih sering dikeluhkan oleh masyarakat Indonesia, salah satunya ialah plak gigi. Kontrol plak merupakan cara efektif mengobati dan mencegah penyakit lainnya pada rongga mulut. Penelitian ini bertujuan untuk mengetahui perbedaan pengetahuan mahasiswa profesi kedokteran Gigi Universitas Jenderal Achmad Yani mengenai kontrol plak gigi berdasarkan jenis kelamin (laki-laki dan perempuan). Jenis penelitian ialah observasional analitik dengan desain potong lintang, dan menggunakan teknik consecutive sampling. Penelitian ini menggunakan non-specialized design of unpaired numerical categorical analysis. Instrumen penelitian menggunakan google form. Data penelitian dianalisis dengan uji T-tidak berpasangan. Hasil penelitian mendapatkan 116 mahasiswa profesi kedokteran gigi sebagai responden, terdiri dari 32 laki-laki (27,6%) dan 84 perempuan (72,4%). Perbandingan pengetahuan responden yaitu rerata pada laki-laki sebesar 21,50±7,030 dan pada perempuan sebesar 22,82±5,928 dengan nilai p=0,311. Simpulan penelitian ini ialah tidak terdapat perbedaan pengetahuan kontrol plak antara kedua jenis kelamin pada mahasiswa profesi kedokteran Gigi Universitas Jenderal Achmad Yani. Kata kunci: jenis kelamin; pengetahuan mengenai control plak